2016
DOI: 10.1177/1060028016678006
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acetaminophen and Ibuprofen Use With Wheezing in Children With Acute Febrile Illness

Abstract: Our study suggests that acetaminophen and ibuprofen are not associated with increased risk for wheezing during acute febrile illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 71 publications
0
19
0
1
Order By: Relevance
“…Of 3933 records identified, 3633 were excluded following title and abstract screening, 276 were excluded following full-text screening, and 4 were ongoing studies. Thus, 19 studies (20 publications 12 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ) were included ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of 3933 records identified, 3633 were excluded following title and abstract screening, 276 were excluded following full-text screening, and 4 were ongoing studies. Thus, 19 studies (20 publications 12 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ) were included ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It may be argued that a single dose of paracetamol is rather harmless. Still, there are reports of adverse effects, and it is an open question whether perfunctory use of analgesics in dentistry should be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…The placebo effect, however, should not be underrated, but perhaps an active substance should not be used for this purpose. Whereas both paracetamol and ibuprofen are widely used for children and adolescents to fight fever and pain, some studies have reported an increased risk of exacerbation of asthma symptoms in children taking paracetamol or ibuprofen. Both pharmaceutical substances also seem to enhance the risk of liver damage in children.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is hardly any evidence for analgesic use, pre-or postoperatively, to reduce pain after uncomplicated dental treatment in children; this remains a knowledge gap. Based on this, and the fact that all administration of pharmacologic agents comes with a risk (Matok et al 2016;Norman et al 2014), it can be questioned if there is any reason for clinical guidelines in this area. Analogously, there is no rationale for introducing or routinely using administration of analgesics in conjunction with routine dental treatments such as filling therapies or uncomplicated extractions (Berlin et al 2018).…”
Section: Discussionmentioning
confidence: 99%